1999
DOI: 10.1172/jci7886
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 2 receptor overexpression activates the vascular kinin system and causes vasodilation

Abstract: Angiotensin II (Ang II) is a potent vasopressor peptide that interacts with 2 major receptor isoforms -AT1 and AT2. Although blood pressure is increased in AT2 knockout mice, the underlying mechanisms remain undefined because of the low levels of expression of AT2 in the vasculature. Here we overexpressed AT2 in vascular smooth muscle (VSM) cells in transgenic (TG) mice. Aortic AT1 was not affected by overexpression of AT2. Chronic infusion of Ang II into AT2-TG mice completely abolished the AT1-mediated press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
386
7
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(420 citation statements)
references
References 56 publications
21
386
7
6
Order By: Relevance
“…Second, because AT 2 effects can be blocked by the specific B 2 antagonist icatibant, other studies have suggested that there might be interactions between AT 2 and the BK/B 2 system. 41,42 Nevertheless, further experiments are needed to arrive at a final conclusion.…”
Section: Impact Ofmentioning
confidence: 99%
“…Second, because AT 2 effects can be blocked by the specific B 2 antagonist icatibant, other studies have suggested that there might be interactions between AT 2 and the BK/B 2 system. 41,42 Nevertheless, further experiments are needed to arrive at a final conclusion.…”
Section: Impact Ofmentioning
confidence: 99%
“…The contribution of such an indirect AT 2 receptor stimulation to the actions of AT 1 receptor antagonists has been demonstrated in experimental models of hypertension, myocardial infarction or heart failure (Gohlke et al 1998;Van Kats et al 2000;Varagic et al 2001). In addition, several studies have revealed a contribution of bradykinin to the AT 1 receptor antagonist actions and suggested that stimulation of the AT 2 receptor leads to a bradykinin-dependent release of NO and subsequent generation of cyclic GMP Carey 1996, 1997;Gohlke et al 1998;Tsutsumi et al 1999).…”
mentioning
confidence: 99%
“…La relation entre l'activation du récepteur AT2 et la production de BK a été confirmée chez la souris surexprimant le récepteur AT2. L'activation du récepteur AT2 entraîne une diminution du pH intracellulaire qui active la kallicréine, induisant ainsi une production accrue de bradykinine aboutissant à la stimulation du RB2 [8].…”
Section: Rôle De La Bradykinine Dans Le Mécanisme D'action Des Iecunclassified